A phase 1b randomized, multicenter, dose determination trial of zelpultide alfa (recombinant human surfactant protein D) in preterm neonates at high risk of developing bronchopulmonary dysplasia - Alonso-Ojembarrena, Almudena; Poindexter, Brenda; Aleem, Samia; Healy, Helen; Aguar-Carrascosa, Marta; Moliner-Calderón, Elisenda; Serrano-Martín, María del Mar; Arroyo, Raquel; Vento, Maximo (Frontiers in Pediatrics, 2025)
BackgroundBronchopulmonary dysplasia (BPD) ranks among the most severe long-term complications of prematurity. Surfactant protein D, not present in commercial surfactant, regulates the innate immune response of the lungs by clearing infectious pathogens and limiting pulmonary inflammation and inflammatory injury. We aimed to assess the safety and tolerability of zelpultide alfa vs. air-sham when added to the standard of care in preterm neonates at risk of BPD. Efficacy was a secondary outcome.MethodsA phase 1b, randomized, double-blind, dose-determination study was conducted that enrolled intubated, mechanically ventilated preterm neonates who required ≥1 surfactant treatment within 96 h of birth. Initially, eight subjects [25–28 6/7 weeks gestational age (GA)] were randomized 3:1 to receive up to two doses of intratracheal zelpultide alfa at each dosing level (2, 4, or 6 mg/kg) or air-sham 24 h apart. Moreover, 12 additional subjects (23–28 6/7 weeks GA) were randomized 3:1 to receive the highest-tolerated dose of zelpultide alfa, or air-sham, once daily for up to 7 days.ResultsIn total, 37 subjects were randomized and treated. Zelpultide alfa, at its highest dose of 6 mg/kg, had a favorable safety profile. Furthermore, 92.9% of zelpultide alfa subjects vs. 100.0% of those that received air-sham experienced ≥1 adverse event. The mortality rate was 21% in the zelpultide alfa group and 0% in the air-sham group, although no deaths were related to the study drug. The incidence of BPD was 32.1% vs. 66.7%, the incidence of BPD or death was 54% and 67%, and time on mechanical ventilation was 17.7 vs. 25.8 days in the zelpultide alfa group compared to the air-sham group, respectively.ConclusionsThis study endorses the safety and tolerability of zelpultide alfa up to 6 mg/kg (≤7 days) and reinforces the need for further clinical development of zelpultide alfa as a therapy for preventing BPD.Clinical Trial Registration: https://clinicaltrials.gov/study/NCT04662151?cond=BPD&term=At-100&rank=1, identifier NCT04662151.